Reconfigurable and programmable origami dielectric elastomer actuators with 3D shape morphing and emissive architectures - Wang, Jiangxin (2021)
Soft actuators with the capability to generate programmable and reconfigurable motions without the use of complicated and rigid infrastructures are of great interest for the development of smart, interactive, and adaptive soft electronic systems. Here, we report a new strategy to achieve a transparent and reconfigurable actuator by using a dielectric elastomer actuator (DEA), which provides mechanical strains under electrical bias, integrated with origami ethyl cellulose (EC) paper that “instructs” the shape changes of the actuator. The actuator can be reconfigured and multiple mechanical motions can be programmed in the device by creating crease patterns that induce variations in the local stiffness to direct the actuations. With the versatile design and fabrication approach, a light emission device with dynamic shape changes was demonstrated.